PULSERA DE CONTROL DE SIGNOS VITALES PARA LOS PACIENTES CON PROBLEMAS DE PRESION ARTERIAL - Andrade Molina, Cesar Enrique (2018)
The monitoring of the Vital Signs (heart rate, body temperature) is of the utmost importance, for people who need this type of controls and can not be done by several factors; either due to lack of time of them or due to mobility problems of the patient; It is for this reason that we will proceed to make a prototype of low cost, so that people who need to perform this type of medical checkups can do so without any problem. In the present work a bracelet is designed to control vital signs (heart rate, body temperature) for patients with blood pressure problems of the Gerontological Center of Good Living in the city of Babahoyo, allowing calls or sending a message in case of detecting some type of irregularity in his vital signs of the patient, by means of the use of Arduino Mega, which allows the connection with the sensors and the GSM SIM 900 module that will allow the connection with mobile telephony networks. In this prototype Arduino will be used, so it will send alerts through text messages and calls that will inform the vital signs of the patient and will reveal what state it is in; if the patient has had some type of fall or his vital signs are past the estimated range, which will allow the person in charge of the patient's care to attend immediately.